Maslinic Acid Attenuates Ischemia/Reperfusion Injury-Induced Myocardial Inflammation and Apoptosis by Regulating HMGB1-TLR4 Axis - Li, Qi; Xu, Mengping; Li, Zhuqing; Li, Tingting; Wang, Yilin; Chen, Qiao; Wang, Yanxin; Feng, Jiaxin; Yin, Xuemei; Lu, Chengzhi (Frontiers in Cardiovascular Medicine, 2021)
Aims: The inflammatory response and apoptosis are the major pathological features of myocardial ischemia/reperfusion injury (MI/RI). Maslinic acid (MA), a natural pentacyclic triterpene with various bioactivities, plays critical roles in multiple cellular biological processes, but its protective effects on pathophysiological processes of MI/RI have not been extensively investigated. This study aimed to determine whether MA treatment alleviate ischemia/reperfusion (I/R)-induced myocardial inflammation and apoptosis both in vitro and in vivo, and further reveal the underlying mechanisms. Methods and Results: The MI/RI rat model was successfully established by ligating the left anterior descending coronary artery and H9c2 cells were exposed to hypoxia/reoxygenation (H/R) to mimic I/R injury. In addition, prior to H/R stimulation or myocardial I/R operation, H9c2 cells or rats were treated with varying concentrations of MA or vehicle for 24 h and 2 consecutive days, respectively. In this study, our results showed that MA could significantly increase cell viability and decrease the cardiac enzymes release after H/R in vitro. MA could significantly improve H/R-induced cardiomyocyte injury and I/R-induced myocardial injury in a dose‐dependent manner. Moreover, MA also suppressed the expression of inflammatory cytokines (TNF-α, IL-1β and IL-6) and the expressions of apoptosis-related proteins (cleaved caspase‐3 and Bax) as well as increased the levels of anti-apoptotic protein Bcl-2 expression both in vitro and in vivo. Mechanistically, MA significantly inhibited nuclear translocation of NF-kB p65 after H/R via regulating HMGB1/TLR4 axis. Conclusion: Taken together, MA treatment may alleviate MI/RI through suppressing both inflammation and apoptosis in a dose-dependent manner, and the cardioprotective effect of MA may be partly attributable to the inactivation of HMGB1/TLR4/NF-kB pathway, which offers a new therapeutic strategy for MI/RI.